COMPARATIVE ASSESSMENT OF HEAVY METAL CONTENT IN SOILS OF INDUSTRIAL ZONES IN UST-KAMENOGORSK (Eurasian Journal of Ecology, 2026)
In the city of Ust-Kamenogorsk, which is the largest industrial center of the East Kazakhstan region, long-term activities of non-ferrous metallurgy and thermal energy enterprises lead to the accumulation of heavy metals in the soil and form foci of sustainable man-made pollution. Among such pollutants, lead (PB), cadmium (Cd), copper (Cu) and zinc (Zn) are especially dangerous because they persist in the soil for a long time, accumulate in Biosystems and pose a serious threat to the ecosystem and human health. The purpose of the study is to determine the actual concentration of heavy metals in the soil in the industrial zones of Ust-Kamenogorsk and compare them with the maximum permissible concentrations (MPC) approved in the Republic of Kazakhstan, as well as assess the level of environmental risk in the region. At the same time, the results obtained make it possible to compare the concentrations recorded in industrial areas with natural levels in the background area, which is important in assessing the real scale of the man-made load. The scientific and practical significance of the study is that it provides new data reflecting the real state of the soil in an area with a high level of industrial pollution and forms the necessary scientific basis for planning environmental measures. The methodology was to take samples from a soil layer at a depth of 0-20 CM, prepare them to use the acid dissolution method according to ISO 11466 standard and determine the concentrations of Pb, Cd, Cu and Zn using atomic absorption spectrometry (AAS).The results showed that in soils in the industrial zone, the content of Pb and Cd exceeds MPC by 5-11 times, Zn and Cu-by 2-5 times, respectively, and the concentrations in the background zone correspond to the standards. Comparison with natural levels detected in the background area proves that the accumulation of heavy metals was formed as a result of man-made impacts characteristic only of industrial points and clearly shows the spatial differences between the sources of pollution. This proves the High man-made impact of industrial facilities and the presence of a risk of heavy metal migration in the region. The value of the study lies in the fact that it provides quantitative data that allows you to determine the exact proportion of polluting sources, conduct environmental monitoring and plan restoration work. The practical significance of the work lies in the fact that the results obtained can be used in the development of programs for environmental assessment of industrial territories, Zoning By risk levels and remediation.Keywords: heavy metals, soil pollution, atomic absorption spectrometry, maximum permissible concentration, Ust-Kamenogorsk.